T cell co-stimulatory and co-inhibitory pathways in atopic dermatitis - Zheng, Chunjiao; Shi, Yuling; Zou, Ying (Frontiers in Immunology, 2023)
The use of immune checkpoint inhibitors (ICIs) targeting the T cell inhibitory pathways has revolutionized cancer treatment. However, ICIs might induce progressive atopic dermatitis (AD) by affecting T cell reactivation. The critical role of T cells in AD pathogenesis is widely known. T cell co-signaling pathways regulate T cell activation, where co-signaling molecules are essential for determining the magnitude of the T cell response to antigens. Given the increasing use of ICIs in cancer treatment, a timely overview of the role of T cell co-signaling molecules in AD is required. In this review, we emphasize the importance of these molecules involved in AD pathogenesis. We also discuss the potential of targeting T cell co-signaling pathways to treat AD and present the unresolved issues and existing limitations. A better understanding of the T cell co-signaling pathways would aid investigation of the mechanism, prognosis evaluation, and treatment of AD.